Bladder cancer and occupation: a case-control study in northern Italy. Issue 1 (January 1996) - Porru, S; Aulenti, V; Donato, F; Boffetta, P; Fazioli, R; Cosciani Cunico, S; Alessio, L
Abstract : OBJECTIVES--A hospital based case-control study was conducted between 1992 and 1993 in the province of Brescia, a highly industrialised area in northern Italy, to evaluate occupational risk factors of bladder cancer. METHODS--The study evaluated 355 histologically confirmed cases of bladder cancer (275 men, 80 women) and 579 controls affected by urological non-neoplastic diseases (397 men, 182 women). Lifetime occupational history, smoking and drinking habits, and sociodemographic characteristics were recorded by means of a structured questionnaire. Odds ratios (ORs) were computed with adjustment for age, smoking, alcohol and coffee consumption, education, and place of residence. RESULTS--A significant (P < 0.05) increase of risk of bladder cancer were found in men for labourers in the construction industry (OR 2.1, 95% confidence interval (95% CI) 1.1-3.9) and for recreational and cultural services (OR 5.0, 95% CI 1.3-18.9). Increased risks, although not significant, were found for various other occupations and industries such as machinery mechanics, metal processers and polishers, blacksmiths, gunsmiths, painters; for transport workers, an increased risk with increasing duration of employment was found. CONCLUSIONS--Occupational exposures seem to contribute to bladder cancer risk in the area under study.